2022
DOI: 10.3389/fimmu.2022.943839
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation and T-cell responses in endometriosis – something other than autoimmunity

Abstract: Endometriosis is defined as the presence of endometrial-like glands and stroma located outside the uterine cavity. This common, estrogen dependent, inflammatory condition affects up to 15% of reproductive-aged women and is a well-recognized cause of chronic pelvic pain and infertility. Despite the still unknown etiology of endometriosis, much evidence suggests the participation of epigenetic mechanisms in the disease etiopathogenesis. The main rationale is based on the fact that heritable phenotype changes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 353 publications
0
23
0
Order By: Relevance
“…In endometriosis, an increased ratio of altered peritoneal macrophages has been indicated, and since they are involved in antigen presentation to CD8 T cells, this points to potentially related dysfunctions within the CD8 T cell compartment. Similarly, changes were found in regulatory T cells (Tregs) in endometriosis, with findings showing an increased number of activated Tregs in the peritoneal fluid of patients with endometriosis ( 93 ). Like macrophages, Tregs are involved in CD8 T cell activation and play an important role in the generation of high-avidity initial responses and effective memory ( 94 ).…”
Section: Discussionmentioning
confidence: 89%
“…In endometriosis, an increased ratio of altered peritoneal macrophages has been indicated, and since they are involved in antigen presentation to CD8 T cells, this points to potentially related dysfunctions within the CD8 T cell compartment. Similarly, changes were found in regulatory T cells (Tregs) in endometriosis, with findings showing an increased number of activated Tregs in the peritoneal fluid of patients with endometriosis ( 93 ). Like macrophages, Tregs are involved in CD8 T cell activation and play an important role in the generation of high-avidity initial responses and effective memory ( 94 ).…”
Section: Discussionmentioning
confidence: 89%
“…Through Pearson analysis, we discovered 25 m6A-regulated mRNAs. Recent studies have demonstrated the impact of SCG2 on the clinical stage, and the influence of macrophage polarization on immunotherapy in colorectal cancer [ 18 , 19 ]. GPC3 [ 20 ] has also been proven to be essential in the immune response, yet no reference has been reported in EM.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic factors are mediators of inflammation and chronic inflammatory disease. Consistently, a disruption of immune cell epigenetic regulation is thus predicted to be a major contributor to unrestrained immune responses and immune tolerance disruption that lead to diseases such as autoimmunity and inflammation [259][260][261]. These epigenetic changes can be caused by smoking, exposure to chemicals, including endocrine-disrupting compounds (EDCs), in the environment, or diet and other lifestyle factors, including sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%